Work Stress and Load as Predictors of Fatigue in Bakery Workers: Implications for Ergonomic Interventions - Yuliani Setyaningsih; Ekawati Ekawati; Ida Wahyuni; Hanifa Maher Denny; Dina Lusiana Setyowati (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: Work-related fatigue poses a significant challenge to worker productivity and well-being, particularly in physically demanding sectors such as the bakery industry. This study investigates the association between psychological stress, physical workload, and work-related fatigue among informal bakery workers in Batang, Indonesia. Methods: A cross-sectional study was conducted involving 52 workers over a two-month period (July–August 2022). Data were collected through direct observation, physiological measurements, and structured questionnaires covering worker characteristics, stress levels, workload (measured via heart rate monitoring), heat stress (WBGT index), and fatigue (measured using a reaction timer). Bivariate analysis (Fisher’s Exact Test) and multivariate logistic regression were performed to identify significant predictors of fatigue. Results: Multivariate analysis showed that both work stress and workload were significantly associated with work-related fatigue. Workers experiencing psychological stress had nearly three times the odds of fatigue (OR = 2.901; p = 0.047), while those with heavy workloads had over nine times the risk (OR = 9.446; p = 0.007). In contrast, heat stress and work tenure were not statistically significant predictors. Conclusion: These findings highlight the critical role of stress and workload in contributing to occupational fatigue. Interventions such as mental health support, ergonomic task redesign, and workload management are essential for improving well-being and safety among informal bakery workers. Future studies should explore additional mediating factors, including coping mechanisms and workplace social support, to inform holistic fatigue prevention strategies.